Investigating the effect of layering and schistosity on the mechanical behavior of rocks using the discrete element method (Rudarsko-geološko-naftni zbornik, 2023)
Anisotropy and deformation in rock material is mainly caused by the non-uniformity and irregular geometry of fracture systems. This factor is among the important problems in designing and evaluating the stability of engineering structures. In this research, the mechanical behavior of layered and schistose rocks is investigated by conducting compressive uniaxial and triaxial strength laboratory tests on rock samples from different directions and angles varying with respect to the loading axis. The tests were carried out on intact blocks of quartz schist rock with 0° layering and invisible schistosity. Next, numerical modelling was performed using the discrete element method (DEM) and calibrating numerical models by laboratory tests. In this process, three types of connections between the minerals (i.e. mica-mica, mica-quartz, and quartz-quartz), the growth of cracks, and the fracture mechanism of layered rocks with different layering angles were investigated. The results showed that unlike the arrangement of the rock particles, the layering angle of quartz schist has an important effect on the mechanical properties of the rock in such a way that uniaxial compressive strength, Young's modulus, cohesion, and internal friction angle respectively have the greatest effect due to the change of the layering angle, while the tensile strength has the least effect.